1999
DOI: 10.1016/s0002-9440(10)65235-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Different Methodological Approaches to the in Vitro Study of Drug-Induced Apoptosis

Abstract: Apoptosis is a dynamic process in which a characteristic morphological or biochemical event used in an assay as a specific marker of apoptosis may be observed over a limited period of time. Asynchronous involvement of cells in apoptosis results in different proportions of apoptotic cells with blebbed membrane, broken nuclei, modified mitochondrial units or fragmented DNA coexisting in the culture at any single moment. Thus, depending on the method used, the extent of apoptosis determined in the same cell popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 46 publications
6
44
0
Order By: Relevance
“…3 F-J). This finding is consistent with the morphological analysis of apoptosis in vitro, which suggests a 2-to 4-h period between the appearance of plasma membrane protrusions to the shedding of blebs of apoptotic cells (27)(28)(29).…”
Section: Visualization Of Single Nerve Cell Apoptosis In Vivosupporting
confidence: 90%
See 3 more Smart Citations
“…3 F-J). This finding is consistent with the morphological analysis of apoptosis in vitro, which suggests a 2-to 4-h period between the appearance of plasma membrane protrusions to the shedding of blebs of apoptotic cells (27)(28)(29).…”
Section: Visualization Of Single Nerve Cell Apoptosis In Vivosupporting
confidence: 90%
“…Despite the fact that our measurement of RGC loss over time is similar to that of previous authors (22)(23)(24)(25)(26), we have recorded much higher rates of detection of RGC apoptosis (15,23,25). Compared with other methods such as DNA fragmentation, morphometry, time-lapse video microscopy, and microculture kinetic assays, annexin 5 has been shown to reveal apoptosis significantly earlier, with positive labeling of cells over a wide range of different stages of the apoptotic pathway (27).…”
Section: Visualization Of Single Nerve Cell Apoptosis In Vivosupporting
confidence: 90%
See 2 more Smart Citations
“…The more recently developed, automated microculture kinetic (MiCK) assay measures sensitivity of tumor cells to chemotherapy using clinical doses of drug by measuring the fraction of cells that have undergone apoptosis. [1][2][3][4] The MiCK assay has been previously tested on cells from patients with acute myeloid leukemia and has been used to direct chemotherapy choice in leukemia patients. 5 Studies comparing clinical criteria to the MiCK assay showed the assay was better able to predict complete remission and survival in acute myeloid leukemia patients.…”
Section: Introductionmentioning
confidence: 99%